2001
DOI: 10.5153/sro.605
|View full text |Cite
|
Sign up to set email alerts
|

The Neglected Art of Hitch-Hiking: Risk, Trust and Sustainability

Abstract: This article explores the sociologically neglected practice of hitch-hiking. It demonstrates the paucity of research on what is potentially a fascinating instance of social interaction and it argues that hitch-hiking provides an interesting test case for the applicability of recent social theories of risk and trust. The reasons for the relative decline in hitch-hiking in Britain are discussed and comparisons are made with continental Europe and the U.S.. The article suggests that despite the increasingly risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Hitchhiking is defined as the act of soliciting rides from strangers as well as a form of transport, in which the hitchhiker tries to get a lift from a random driver, usually a car or truck driver, for free without prior arrangement and as a one-way trip, usually not involving a change of an initial route (Vedernikov, Kulik, & Ramamohanarao, 2016). Though the phenomenon of hitchhiking was widespread in the 1960s and early 1970s, it lost popularity over time due to different factors (Chesters & Smith, 2001;O'Regan, 2013). However, a new generation of hitchhikers has emerged modernising hitchhiking, giving it new meanings, and figuring out new methods to deal with the challenges hitchhikers face (Kendall, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hitchhiking is defined as the act of soliciting rides from strangers as well as a form of transport, in which the hitchhiker tries to get a lift from a random driver, usually a car or truck driver, for free without prior arrangement and as a one-way trip, usually not involving a change of an initial route (Vedernikov, Kulik, & Ramamohanarao, 2016). Though the phenomenon of hitchhiking was widespread in the 1960s and early 1970s, it lost popularity over time due to different factors (Chesters & Smith, 2001;O'Regan, 2013). However, a new generation of hitchhikers has emerged modernising hitchhiking, giving it new meanings, and figuring out new methods to deal with the challenges hitchhikers face (Kendall, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding agreeableness, its facets encompass trust, straightforwardness, altruism, compliance, modesty, and tender-mindedness (John & Srivastava, 1999). Whilst hitchhiking the hitchhiker will learn to trust more people without being judgmental about looks, religion, origin or culture of their drivers (Chesters & Smith, 2001). The hitchhikers also have to display an agreeable attitude towards the drivers, which could help to maximize feelings of interest and safety and minimize those of danger in the driver (Morgan, Lockard, Fahrenbruch, & Smith, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.4 Mentions of the Internet in passing, as a cultural site, a way of communicating or a source of representations were made by, among others, Bancroft (1999), Buttel (1999), Linden (1999), Nerlich et al (1999, Winter (2000), Boden (2001), Chesters and Smith (2001), Dunne (2001), Lyon (2001), Walliss (2002), Allen (2003), Deem andJohnson (2003), Hunt (2003), Misztal (2003) and Heather (2004). Clearly the Internet is becoming embedded into sociology as a site of social life and conduit of social interaction that does not always need to be specifically marked out for comment.…”
Section: Introductionmentioning
confidence: 99%
“…As a social and cultural phenomena, hitchhiking became popular in 1940s and 1960s and consequently attracted many studies from sociological and psychological point of view [4]. For example, [5] experimentally showed that females attract approximately 3 times more cars to stop than males, while eye contact doubled this chance for both genders.…”
Section: Hitchhikingmentioning
confidence: 99%